The Effect of All-Trans Retinoic Acid Supplementation to Periodontitis - Praptiwi Hanafi; Enik Sulistyowati; Kustiono Kustiono (Jurnal LINK, 2012)
Vitamin A metabolite all-trans retinoic acid (ATRA), regulates periodontal collagen synthesis. Type 1 collagen, main component of periodontium was destroyed in perio-dontitis. Objectives: to study the effect of ATRA to body weight (BW), periodontal struct-ure, ATRA concentration, and collagen status. Method: 26 Wistar adult male rat of 8 weeks were used in the experimental study with Rancangan Acak Lengkap. Randomly chosen samples were devided into induced periodontitis through Porphyromonas gingivalis innoculation, and not induced. Tetracycline of 18.36 mg/day were given beginning from the finding of periodontitis, for 8 days. Randomly chosen samples were given ATRA 100 and 1000 µg/day, with A0 group as control. Body weight were measured using digital balance, periodontal tissue with light microscope, tissue ATRA concentration with High Performance Liquid Chromatography, collagen status i.e synthesis and degradation with Reverse Transcriptase Polymerizing Chain Reaction, spectrophotometry UV-VIS and Thin layer chromatography. T test was used to analyze BW mean difference among 3 groups before, also after ATRA supplementation. ANOVA was used to analyze BW and collagen status after ATRA supplementation. Result: There were no significant difference BW before and after supplementation (p=0.063 and 0.804). All-trans retinoic acid improves the collagen fiber structure. Amount of ATRA and RNA were not yet measured due to lack of time, technician instrument-ation, while they were needed to gain more measurable data.